When the Latin American constitutional judge forgets his/her job of conventionalization of law: reflections about a recent sentence of the Argentine Supreme Court of Justice - Espinosa-Saldaña Barrera, Eloy (2017)
In this article, the author tell us about the job of the constitutional judge and the importance that this takes in a context of crisis. Also, he highlights the conventionalization of law as the central task of constitutional judges. Likewise, he details the difficulties involved in this task and the challenges to be faced for the consolidation of a common law in Latin America.